2001
DOI: 10.1080/09629350123338
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of IgE turnover in non‐sensitized and sensitized rats

Abstract: BACKGROUND: Although the levels of immunoglobulin E (IgE) in the circulating blood are often elevated in patients with allergic diseases, such levels cannot always be considered as pathognomonic signs of allergy. The induction of allergic reactions in the tissue was inferred to be related to the amount of IgE passing through the vascular wall. AIMS: We attempted to clarify which compartment, the intravascular or extravascular, plays an important role in the regulation of the turnover of rat IgE. METHODS: The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…administration in rats irrespective of the sensitized state. 1 In the present study, we demonstrated that the levels of monoclonal DNP-specific rat IgE underwent a rapid decrease in the suplatast-administered or azelastine-administered group in comparison with those of the distilled water-administered group under non-sensitized conditions at 15 min-3 h following administration of IgE. Pharmacokinetic analysis revealed that the values of the distribution half-life (t 1/2 a) in the suplatast-administered or azelastineadministered group were smaller than those of the distilled water-administered group irrespective of the sensitized state, suggesting that the anti-allergic drugs used can facilitate the excretion of IgE from the circulation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…administration in rats irrespective of the sensitized state. 1 In the present study, we demonstrated that the levels of monoclonal DNP-specific rat IgE underwent a rapid decrease in the suplatast-administered or azelastine-administered group in comparison with those of the distilled water-administered group under non-sensitized conditions at 15 min-3 h following administration of IgE. Pharmacokinetic analysis revealed that the values of the distribution half-life (t 1/2 a) in the suplatast-administered or azelastineadministered group were smaller than those of the distilled water-administered group irrespective of the sensitized state, suggesting that the anti-allergic drugs used can facilitate the excretion of IgE from the circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Calculation of kinetic parameters was performed as previously described. 1 Statistical analysis was performed by the unpaired Student's t-test for betweengroup comparisons. Data are expressed as mean ± standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations